PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KESULITAN KEUANGAN PADA PERUSAHAANREAL ESTATE DAN PROPERTYYANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2014 - Maya Lailatul Zannah; Azwir Nasir; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study was to determine the effect size of the audit committee, the independence of audit committee members, meeting frequency of audit, competence and size of the company's audit committee of the company's financial difficulties on the Real Estate and Property in BEI.The population in this study is the overall Real Estate and Property companies listed in the Indonesia Stock Exchange (BEI) in 2014. The sample in this study as many as 32 companies. In examining the relationship of independent variables (X) and the dependent variable (Y) in this study, data analysis method used logistic regression independent variables is a combination of a continuous variable (metric data) and categorical (data non-metric) with SPSS (Statistical Product and Service Solution). The result of this research indicates that the frequency of audit committee 0.031, competence of the audit committee 0.015, and company’s financial difficultie 0.029 significant of the financial difficulties, meanwhile audit committee 0.338, and independence of the audit committee 0.247 has no significant impact of the financial difficulties.Keywords : Audit, Financial Difficulties, Real Estate and Property Company, and Indonesia Stock Exchange